The New Incorporation of Video Art and Video Poetry during the COVID-19 Pandemic: A Matter of Myth or Existing Reality - Bernaschina, Diego (Cultural Arts Research and Development, 2022)
This paper corresponds to an interdisciplinary investigation based on literature, art and new media to involve own experiences of video work and study of the health crisis between 2020 and 2021 in Spain. The main goal is to investigate the sample of the three videos produced on the coronavirus pandemic, creating a social dialogue to incorporate media arts together with literary arts. It is important to propose the two pieces of video, both the poem or the art discourse and the audiovisual technology to integrate the artwork’s interdisciplinary. Based on this discussion, it consists of a referential account of creative thinking toward the pain of patients in times of COVID-19. In conclusion, this incorporation of video art and video poetry, mainly, is facilitated to give the experimentation of artworks the opportunity to collaborate in the interdisciplinary or transdisciplinary project, depending on the connection or link between art and literature.